2005
DOI: 10.1055/s-2005-915604
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Treatment of Quadrigeminal Cistern Arachnoid Cysts

Abstract: Five patients with arachnoid cysts of the quadrigeminal cistern treated by endoscopic fenestration are reported and another eleven well-documented cases from the literature are reviewed. Among the five personal cases four were children and one was adult; the cyst fenestration was performed from the lateral ventricle in three cases and from the third ventricle in two. In four patients the endoscopic treatment resulted in clinical remission, whereas a two-month-old baby later required a shunt. The lateral ventri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 13 publications
1
23
0
Order By: Relevance
“…Failures of endoscopic fenestration, either alone or in combi- nation with third ventriculostomy, have been reported in the literature [3,14,21].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Failures of endoscopic fenestration, either alone or in combi- nation with third ventriculostomy, have been reported in the literature [3,14,21].…”
Section: Discussionmentioning
confidence: 99%
“…With the extent of the indications for ventricular endoscopy, the neuroendoscopic approach to quadrigeminal cysts has gained increasing acceptance. Several authors have reported cases [1,4,5,[9][10][11][12][15][16][17][18][19][20] or series [3,5,13] of neuroendoscopic quadrigeminal cyst treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Symptomatic arachnoid cysts located in the cerebellopontine angle and quadrigeminal cisterns are rare, and may manifest as trochlear nerve paresis, trigeminal neuralgia, hemifacial spasm, and normal pressure hydrocephalus. 1,4,6,9) Multiple intracranial arachnoid cysts located at different sites are extremely rare. Very few cases of asymptomatic multiple arachnoid cysts involving five different locations in the cranial cavity have been documented.…”
Section: Introductionmentioning
confidence: 99%